Criteria for nonlinear parameters of relativistic mean field models - Sulaksono, A.; Bürvenich, T. J.; Reinhard, Paul-Gerhard; Maruhn, J. A. (Physical Review C - Nuclear Physics, 2009)
Based on the properties of the critical and the actual effective masses of sigma and omega mesons, criteria to estimate the values of the isoscalar nonlinear terms of the standard relativistic mean field model that reproduce stable equations of state in respect to particle hole excitation at high densities are derived. The relation between nuclear matter stability and the symmetric nuclear matter properties are shown. The criteria are used to analyze in a more systematic way the high-density longitudinal and transverse instabilities of some parameter sets of relativistic mean field models. The critical role of the vector and vector-scalar nonlinear terms is also discussed quantitatively. © 2009 The American Physical Society.
CRIS-Team Scopus Importer:2023-07-24